Gas injection in fractured reservoirs : emphasis on mass transfer - Mohammadzadeh Bahar, Mohammad (Curtin University, 2010)
Mass transfer occurs in a number of Enhanced Oil Recovery (EOR) processes such as gas injection, solvent injection, Water Alternative Gas injection (WAG) processes and gas cycling. The role of mass transfer in gas injection into an oil phase at fractured media is significant. In naturally fractured reservoirs, fluid exists in two interconnected systems; the rock matrix, which contains the bulk of the volume of the oil reservoir, and the high permeability fractures medium.Laboratory measurements of the diffusion coefficient of methane into crude oil under both unsteady-state and steady-state conditions were carried out to obtain the dissolution rates of methane during gas injection and/or flooding in the short term, and for enhanced oil recovery at thermodynamic equilibrium in the long term. The pressure drop in the core flooding cell during the contact of the methane and oil phases was used to measure the diffusion coefficient of the system under the reservoir conditions. A new empirical correlation for the diffusion coefficient was achieved using the measured experimental data at reservoir conditions. A comparison of this new correlation and previous methods shows that the current method is more accurate than other methods at high pressure and temperature conditions.Experimental tests on fluid flow in tight carbonate porous media were carried out with single and composite core plugs. It was demonstrated that the swelling of oil strongly depended on the contact time of the oil and gas phases and heterogeneity of the system.The two and three-phase relative permeability in tight carbonate reservoirs was a major part of this research. It was carried out on single and composite core plugs at reservoir conditions. Modelling of the displacement of fluids in tight carbonate rocks was carried out with experimental data. Solving of the partial differential equation of displacement phenomena in porous media was carried out with the finite element method software (FLEXPDE). All of the experimental data with the new diffusion coefficient correlation were used to model the system.In the fracture medium, an artificial fracture in synthetic rock was made and all the parameters used for carbonate rock were considered without fracture. Modelling of the system was carried out between the matrix and fracture medium. The effect of mass transfer between gas in the fracture and oil in the matrix was evaluated and the variation of saturation in the matrix by applying the boundary condition method was evaluated. As a result, it was shown that the mass transfer significantly increased the recovery from the matrix by following the condensation and evaporation mechanisms.